PRAKTEK KAFAAH DI LINGKUNGAN PONDOK PESANTREN - Luthfia, Chaula; Pratama, Rizal Dian (LPPM Universitas Bina Bangsa, 2024)
The high rate of divorce that occurs today where most of the causes are the inequality between husband and wife. The concept of kafa'ah in Islam is a solution to minimize the occurrence of divorce. The purpose of this study is to see the implementation of the kaf'ah concept in the Islamic boarding school environment of Benda Village, Sirampog District, Brebes Regency. This research is a field research with a normative approach. The result of this research is the concept of kafa'ah or comparable or commensurate applied in the pesantren environment of Benda Village, Sirampog District, aims to create harmony so that later there will be compatibility, balance and continuity between the two parties who will undergo the household ark. Although Benda Village, Sirampog District is an area that upholds high religious social values because it is located in the Islamic boarding school environment. However, the concept of kafa'ah that is applied is not only based on religious similarities. There are several criteria that are considered important also in choosing and determining a partner. Among them are similarities in work, nasab, property, education and physical. This similarity does not contradict the concept of kafa'ah stipulated in Islam. But sekufu in religion becomes the first and foremost measure. This concept is clearly believed and applied as a logical consequence of Islamic law. In addition, being in the Islamic boarding school environment also has an influence on the selection of religion as the first and main order in choosing and determining a partner. Another criterion is used as an additional measure that then does not rule out sekufu in religion